North Dakota’s Experience with the Academy Model: A Successful Replication - Tom Hall; Ann Clappe (Educational Considerations, 2016)
Leadership is a key factor in improving schools and ensuring academic success for all students. At the building level, the leadership role has traditionally been assigned to the principal, but principals cannot be expected to be the sole leaders in their buildings.
Keywords: Leadership; Challenges; Kansas; education; United School Administrators; development; North Dakota; Replication